2018
DOI: 10.1093/wber/lhx020
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Poor vs. Measuring Their Poverty: Exploring the Drivers of Targeting Effectiveness in Indonesia

Abstract: Centralized targeting registries are increasingly used to allocate social assistance benefits in developing countries. There are two key design issues that matter for targeting accuracy: (i) which households to survey for inclusion in the registry; and (ii) how to rank surveyed households. We attempt to identify their relative importance by evaluating Indonesia's Unified Database for Social Protection Programs (UDB), among the largest targeting registries in the world, used to provide social assistance to over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 26 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…For a number of variables to be used as a poverty proxy, Grosh and Baker (1995) studied by using Living Standards Measurement Survey data in Jamaica, Bolivia and Peru, where they found that more information was preferred to less, although there were diminishing returns for more information added. This diminishing return also found in study by Bah, Bazzi, Sumarto, and Tobias (2018) where she found that out of 340 candidate variables, using a model random sampling method to select good predictions of household welfare in Indonesia, the best model to predict poverty in terms of undercoverage rate was the model with total 20 predicting variables. Also, Schreiner (2008aSchreiner ( , 2009Schreiner ( , 2010aSchreiner ( , 2011Schreiner ( , 2012aSchreiner ( , 2016 developed a Poverty Probability Index (PPI) to be used as a poverty scorecard by using only 10 household characteristic variables to simplify the questionnaire and to reduce cost of data collecting.…”
Section: Pmtmentioning
confidence: 63%
“…For a number of variables to be used as a poverty proxy, Grosh and Baker (1995) studied by using Living Standards Measurement Survey data in Jamaica, Bolivia and Peru, where they found that more information was preferred to less, although there were diminishing returns for more information added. This diminishing return also found in study by Bah, Bazzi, Sumarto, and Tobias (2018) where she found that out of 340 candidate variables, using a model random sampling method to select good predictions of household welfare in Indonesia, the best model to predict poverty in terms of undercoverage rate was the model with total 20 predicting variables. Also, Schreiner (2008aSchreiner ( , 2009Schreiner ( , 2010aSchreiner ( , 2011Schreiner ( , 2012aSchreiner ( , 2016 developed a Poverty Probability Index (PPI) to be used as a poverty scorecard by using only 10 household characteristic variables to simplify the questionnaire and to reduce cost of data collecting.…”
Section: Pmtmentioning
confidence: 63%
“…This literature includes studies [ 33 , 34 ] using Randomised Control Trial (RCT) methods in a select group of villages, and nationally representative studies that have, for example the Askeskin and Jamkesmas programs [ 35 , 36 ] or the Raskin program [ 37 , 38 ]. Others evaluate the complementarity of various social welfare programs, and examine whether they reached the intended beneficiaries [ 39 , 40 ]. However, the focus of this literature has been on the targetting of social welfare programs for poor households, and not on a nation-wide reform of governance and fiscal transfers to rural villages.…”
Section: Introductionmentioning
confidence: 99%
“…This study addresses two limitations of the predominant proposal to combine carbon pricing with cash transfers in the context of low-and middle-income countries. First, while lump-sum cash transfers are effective in theory and may entail several benefits for economic development (Bastagli et al 2019), existing cash transfer programs may be imperfect instruments to channel money to households in practice: Existing cash transfer programs are imperfectly targeted (e.g., reach richer households), and suffer from imperfect coverage (e.g., do not reach all poor households) (Robles et al 2019;Bah et al 2019). It is therefore not clear if existing cash transfer programs can play the role in practice that lumpsum rebates play in theory (Malerba et al 2021;Vogt-Schilb et al 2019;Renner 2018).…”
Section: Introductionmentioning
confidence: 99%